NATURE EXPLOITATAION IN MOANA: AN ECOCRITICISM PERSPECTIVE - Eka Syamratul Fikriyah Agusta Akhiyat (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
Disney movie Moana has broadly analyzed in many journals portrayed through lenses of ecological study, but none of them take more focus on the process of reconciliation with nature yet. The movie brings up the issue of nature exploitation caused by human greed that does not think of the adverse impacts. This paper is a part of a film study that analyzes the process of reconciliation with nature using an ecocritical perspective to examine the nature exploitation and the process of reconciling the balance of nature in Moana. The study reveals that nature exploitation is portrayed when Maui steals the stone from Te Fiti that contains a super power that can create life, which creates the scarcity of natural resources on each island. Furthermore, the study shows that Moana is on the ecocentric side and shows ecocentric attitudes toward related environmental issues. The results of this study reveal that Moana not only cared about nature but also valued them as entities with a life force. She leads the reconciliation process to restore the balance with nature.